Mental Health and Victimization: Does Risky Lifestyle Matter? - Azimi, Andia M. (Journal of interpersonal violence, 2021)
Research shows that individuals with mental health problems are at an increased risk of victimization compared with individuals without such problems, and certain mental health problems are linked with particular types of victimization. Although most research has not used theory to guide why these differential risks exist, researchers have begun to theorize the reasons why individuals with mental health problems experience victimization. In line with these recent inquiries, the present study uses a Lifestyle/Routine Activities perspective to examine the victimization of people with mental health problems. Further, different types of mental health problems are explored for their potential links to victimization. Risky lifestyle factors are also explored for their potential mediating role in the link between mental health and victimization. A path analysis is conducted with data from the National Longitudinal Study of Adolescent to Adult Health (Add Health). Results suggest that different mental health problems have differing links to victimization types, and lifestyle factors mediate the link for some forms of victimization. The findings imply that certain lifestyle factors explain victimization risk among people with mental health problems, but these individuals may also have unique risk factors related to mental health. Policy implications and directions for future research are discussed.